Management of ALL in adults: 2024 ELN recommendations from a European expert panel - Gökbuget, Nicola; Boissel, Nicolas; Chiaretti, Sabina; Dombret, Hervé; Doubek, Michael; Fielding, Adele; Foà, Robin; Giebel, Sebastian; Hoelzer, Dieter; Hunault, Mathilde; Marks, David I; Martinelli, Giovanni; et al. (Blood, 2024)
Experts from the European Leukemia Net (ELN) working group for adult acute lymphoblastic leukemia have identified an unmet need for guidance regarding management of adult acute lymphoblastic leukemia (ALL) from diagnosis to aftercare. The group has previously summarized their recommendations regarding diagnostic approaches, prognostic factors, and assessment of ALL. The current recommendation summarizes clinical management. It covers treatment approaches, including the use of new immunotherapies, application of minimal residual disease for treatment decisions, management of specific subgroups, and challenging treatment situations as well as late effects and supportive care. The recommendation provides guidance for physicians caring for adult patients with ALL which has to be complemented by regional expertise preferably provided by national academic study groups.
Keywords: management nemoci; Neoplasm, Residual; Evropa; Humans; lidé; Precursor Cell Lymphoblastic Leukemia-Lymphoma; dospělí; Disease Management; Prognosis; Europe; Adult; akutní lymfatická leukemie; prognóza; reziduální nádor